Boosting Antioxidant Quality in Cucumber Beverages with Encapsulated Tomato Carotenoids - Laleh Mozafari; Lorena Martínez-Zamora; Marina Cano-Lamadrid; Perla A. Gómez; Francisco Artés-Hernández (Antioxidants)
Tomato by-products are widely generated during processing, which deserve revalorization due to being rich in bioactive compounds that can be incorporated into novel formulas. This study explores the use of tomato by-products as a source of pigments and antioxidant compounds to develop a seasoned cucumber beverage enriched with encapsulated carotenoids. Extracts from industrial tomato pomace were obtained using ultrasound-assisted extraction (USAE) and accelerated solvent extraction (ASE), and then encapsulated by spray-drying with inulin (I), maltodextrin (M), or a maltodextrin–inulin blend (MI). The powders were added to a cucumber beverage treated with high hydrostatic pressure (HHP) and stored for 28 days at 4 °C. Physicochemical properties, microbial load, carotenoid content (U-HPLC), free phenolic content (FPC), and total antioxidant capacity (TAC) were monitored. Beverage samples with maltodextrin (ASE-M, USAE-M) and the maltodextrin–inulin blend (ASE-MI, USAE-MI) showed superior color stability and pH maintenance. USAE-MI achieved the highest TAC at the end of storage and ensured microbial safety by reducing mesophilic bacteria, molds, and yeast. During storage, FPC declined (to ~3.5–5 mg 100 mL−1), TAC increased (to ~16–20 mg 100 mL−1), and carotenoid was kept stable (~9–13 mg L−1). These results highlight the potential of combining HHP with tomato by-product encapsulates to improve the shelf life, quality, pigment stability, and antioxidant properties of vegetable-based beverages.